Artificial Intelligence in Pharmaceutical Regulatory Affairs: An Introduction - Chandrasekaran, Kumar; Kumar, T M Pramod; V, Balamuralidhara (Asian Journal of Biological and Life Sciences, 2025)
Navigating the pharmaceutical regulatory landscape is notoriously time-intensive, primarily due to its intricate nature and constant evolution. Traditional approaches to regulation are often cumbersome and slow, whereas Artificial Intelligence (AI) has already made significant inroads into various facets of the pharmaceutical industry. AI is now poised to transform pharmaceutical regulatory affairs, a critical domain responsible for overseeing drug approval processes, ensuring compliance with regulatory standards, and facilitating communication with regulatory bodies. This field is marked by its complexity, vast data requirements, and the necessity for precise accuracy, all of which pose substantial challenges. AI brings innovative solutions to the table, significantly improving efficiency, accuracy, and strategic decision-making. This article aims to introduce the foundational aspects of AI in pharmaceutical regulatory affairs by highlighting the key areas where AI is making an impact, the challenges and considerations involved, and the benefits it brings to the table. Ultimately, AI offers transformative potential for pharmaceutical regulatory affairs, addressing its inherent challenges and fostering advancements in efficiency, precision, and strategic planning.
Keywords: Artificial Intelligence; Pharmaceutical regulatory affairs